Interleukin 35 Polymorphisms Are Associated with Decreased Risk of Premature Coronary Artery Disease, Metabolic Parameters, and IL-35 Levels: The Genetics of Atherosclerotic Disease (GEA) Study - Rosalinda Posadas-Sánchez; Nonanzit Pérez-Hernández; Javier Angeles-Martínez; Fabiola López-Bautista; Teresa Villarreal-Molina; José Manuel Rodríguez-Pérez; José Manuel Fragoso; Carlos Posadas-Romero; Gilberto Vargas-Alarcón (Hindawi Limited, 2017)
Interleukin 35 (IL-35) is a heterodimeric cytokine involved in the development of atherosclerosis. The aim of the present study was to establish if the polymorphisms of IL-12A and EBI3 genes that encode the IL-35 subunits are associated with the development of premature coronary artery disease (CAD) in Mexican individuals. The IL-12A and EBI3 polymorphisms were determined in 1162 patients with premature CAD and 873 controls. Under different models, the EBI3 rs428253 (OR = 0.831, Padd = 0.036; OR = 0.614, Prec = 0.033; OR = 0.591, Pcod2 = 0.027) and IL-12A rs2243115 (OR = 0.674, Padd = 0.010; OR = 0.676, Pdom = 0.014; OR = 0.698, Phet = 0.027; OR = 0.694, Pcod1 = 0.024) polymorphisms were associated with decreased risk of developing premature CAD. Some polymorphisms were associated with clinical and metabolic parameters. Significant different levels of IL-35 were observed in EBI3 rs4740 and rs4905 genotypes only in the group of healthy controls. In summary, our study suggests that the EBI3 and IL-12A polymorphisms play an important role in decreasing the risk of developing premature CAD; it also demonstrates the relationship of the EBI3 rs4740 and rs4905 genotypes with IL-35 levels in healthy individuals.